Application of alumina substrate in friction catalytic degradation of high-concentration organic dye wastewater

By using alumina ceramic sheets as substrates and titanium dioxide nanopowders as catalysts in the friction catalytic system, the problem of low wastewater treatment efficiency of high-concentration organic dyes in the prior art is solved, and efficient and rapid organic dye degradation is achieved.

CN119504001AInactive Publication Date: 2025-02-25LUOYANG NORMAL UNIV

Patent Information

Application Number
CN202510091167.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is inefficient in treating high-concentration organic dye wastewater, and the existing friction catalysis technology takes time, limiting its large-scale application.

Method used

In the system of friction catalytic degradation of organic dye wastewater, an alumina ceramic sheet is used as the substrate and titanium dioxide nanopowder is combined as a catalyst to achieve efficient degradation of organic dyes through friction catalysis.

Benefits of technology

By using alumina ceramic sheets as the substrate, the degradation rate of organic dyes is significantly improved, the time for complete degradation is shortened, and the high concentration of organic dye wastewater of 20~30 mg/L can be effectively treated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504001A_ABST
    Figure CN119504001A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of friction catalysis, and particularly relates to application of an aluminum oxide substrate in friction catalytic degradation of high-concentration organic dye wastewater, an aluminum oxide ceramic chip is used as a substrate, titanium dioxide nano powder is used as a catalyst, and the aluminum oxide ceramic chip is fixed at the bottom of a flat-bottom glass beaker; the method comprises the following steps: adding organic dye wastewater, a magnetic turntable and titanium dioxide nano powder into a flat-bottomed glass beaker, then putting the flat-bottomed glass beaker in a dark environment at room temperature, stirring and reacting on a magnetic stirrer for 90-150 minutes, and after the reaction is completed, completely degrading organic dye in the wastewater. According to the method, the aluminum oxide ceramic chip is added into a system for performing friction catalytic degradation on the organic dye wastewater by using the titanium dioxide nano powder as the substrate, so that the degradation rate of the organic dye is greatly improved, the complete degradation time of the organic dye is shortened, and a new thought is provided for performing friction catalytic degradation on the organic dye wastewater by using the titanium dioxide nano powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of friction catalysis, and in particular relates to application of an aluminum oxide substrate in friction catalytic degradation of high-concentration organic dye wastewater. Background Art

[0002] my country's dye production is about 900,000 tons per year, of which about 20% are directly discharged into water bodies without proper treatment during preparation, finishing and use, causing serious harm to the ecological environment. Methyl orange and methylene blue, as typical anionic and cationic dyes, are usually found in the wastewater discharged from the textile, leather and printing and dyeing industries. Due to their high chroma, high biological toxicity and difficulty in biodegradation, dye wastewater containing methyl orange and methylene blue will not only inhibit the photosynthesis of aquatic plants, but also directly poison aquatic organisms, thereby seriously damaging the aquatic system.

[0003] There are many methods for treating dye wastewater, including physical, electrochemical, photocatalytic and biological methods. Although these methods have been proven to be effective in solving the problem of dye wastewater treatment, they do have certain disadvantages. Physical adsorption methods cannot decompose or eliminate pollutants, and pollutants still coexist with the environment. Chemical treatment methods require the consumption of additional chemical energy and electrical energy. Photocatalytic processes rely on stable light sources and are limited by external environmental conditions, which limits their continuous operation. Biological methods have low operating efficiency.

[0004] As an emerging catalytic technology, tribocatalysis has many advantages. It can collect tiny mechanical energy in the environment, such as water flow disturbance and mechanical vibration, to achieve catalytic reactions. It does not require additional energy such as electricity and light energy, which can effectively reduce energy consumption and save costs. In addition, tribocatalysis technology also has the advantages of simple equipment and easy operation. It does not require complex reaction equipment and harsh reaction conditions, and is easy to achieve industrial application and large-scale promotion. The current tribocatalytic wastewater degradation technology is time-consuming, which limits its large-scale application. Summary of the invention

[0005] The purpose of the present invention is to provide an application of an aluminum oxide substrate in the friction catalytic degradation of high-concentration organic dye wastewater. Alumina ceramic sheets are added as substrates in the system of titanium dioxide nanopowder friction catalytic degradation of organic dye wastewater, which not only improves the degradation rate of organic dyes and shortens the time for complete degradation of organic dyes, but also can be used for the degradation of high-concentration organic dye wastewater, providing an efficient treatment method for the degradation of high-concentration organic dye wastewater.

[0006] The present invention firstly proposes an application of an aluminum oxide substrate in friction catalytic degradation of high-concentration organic dye wastewater.

[0007] The aforementioned alumina substrate is used in the friction catalytic degradation of high-concentration organic dye wastewater. The alumina substrate is an alumina ceramic sheet. The thickness of the alumina ceramic sheet can be 1 mm, but is not limited to the above size.

[0008] Specifically, in the above application, alumina ceramic sheets are used as substrates and titanium dioxide nanopowder is used as catalysts to achieve degradation of organic dye wastewater by friction catalysis. The specific degradation method includes: fixing an alumina substrate at the bottom of a flat-bottomed glass beaker, then adding organic dye wastewater, a magnetic turntable and titanium dioxide nanopowder into the flat-bottomed glass beaker, then placing the flat-bottomed glass beaker in a dark environment at room temperature (25°C), stirring the reaction on a magnetic stirrer for 90 to 150 minutes, and after the reaction is completed, the organic dye in the wastewater is completely degraded.

[0009] Furthermore, the aluminum oxide substrate is fixed to the bottom of the flat-bottomed glass beaker by gluing. The aluminum oxide substrate can be glued with commercially available 502 glue, but is not limited to the above gluing method.

[0010] Furthermore, the bottom of the flat-bottomed glass beaker is round, the alumina substrate is round, and the size of the alumina substrate is slightly smaller than the size of the bottom of the flat-bottomed glass beaker. For example, the diameter of the alumina substrate is about 1 cm smaller than the diameter of the bottom of the flat-bottomed glass beaker, but the above description is not considered to be a limitation of the present invention.

[0011] The aforementioned alumina substrate is used in the friction catalytic degradation of high-concentration organic dye wastewater, and the magnetic turntable adopts the magnetic turntable disclosed in Patent No. 202011431424.5 or Patent No. 202022946950.7.

[0012] The aforementioned aluminum oxide substrate is used in the friction catalytic degradation of high-concentration organic dye wastewater, wherein the concentration of the organic dye in the organic dye wastewater is 20-30 mg / L.

[0013] The aforementioned aluminum oxide substrate is used in the friction catalytic degradation of high-concentration organic dye wastewater, wherein the organic dye in the organic dye wastewater is at least methyl orange or methylene blue, but is not limited to methyl orange or methylene blue.

[0014] In the application of the aforementioned alumina substrate in the friction catalytic degradation of high-concentration organic dye wastewater, too high or too low rotation speed of the magnetic stirrer will affect the degradation effect, and the rotation speed is preferably set to 400 rpm.

[0015] The aforementioned alumina substrate is used in the friction catalytic degradation of high-concentration organic dye wastewater, and the ratio of the mass of the titanium dioxide nanopowder to the volume of the organic dye wastewater is 10 mg: 1 mL, that is, the mass of the titanium dioxide nanopowder added to every 1 mL of organic dye wastewater is 10 mg, and the mass of the titanium dioxide nanopowder added to every 10 mL of organic dye wastewater is 100 mg.

[0016] The aforementioned aluminum oxide substrate is used in the friction catalytic degradation of high-concentration organic dye wastewater, and the particle size of the titanium dioxide nanopowder is 30-50 nm.

[0017] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages: (1) Add 30 mL of 30 mg / L methyl orange solution or 30 mL of 20 mg / L methylene blue solution to a flat-bottomed glass beaker (equivalent to a glass substrate), and add a magnetic turntable and 300 mg of titanium dioxide nanopowder. Stir magnetically in a dark environment at room temperature (25°C). The time for the friction catalysis of titanium dioxide nanopowder to completely degrade methyl orange and methylene blue is 420 min and 15 h, respectively. After sticking a titanium metal sheet to the bottom of the flat-bottomed glass beaker as a substrate, the degradation rate of methyl orange and methylene blue can be effectively accelerated. Under the same conditions, the time for complete degradation of methyl orange and methylene blue is shortened to 360 min and 4.5 h, respectively. After replacing the titanium substrate with an alumina ceramic sheet as the substrate, the degradation rate of methyl orange and methylene blue is greatly accelerated, and the time for complete degradation is further shortened. Under the same conditions, the time for complete degradation of methyl orange and methylene blue is shortened to 120 min and 2.5 h, respectively. It is fully demonstrated that adding alumina ceramic sheets as substrates in the system of friction catalytic degradation of methyl orange or methylene blue wastewater by titanium dioxide nanopowder can greatly increase the degradation rate of methyl orange or methylene blue and shorten the time for complete degradation of methyl orange or methylene blue. This shows that alumina substrates can promote the friction catalytic degradation process and have great application potential in the treatment of organic dye wastewater.

[0018] (2) The present invention adds alumina ceramic sheets as a substrate to the system of titanium dioxide nanopowder friction catalytic degradation of organic dye wastewater, which not only improves the degradation rate of organic dyes and shortens the time for complete degradation of organic dyes, but also can be used for the degradation of high-concentration organic dye wastewater. The organic dye concentration of organic dye wastewater suitable for existing photocatalytic degradation of organic dye wastewater is generally about 10 mg / L, while the present invention can be used for the degradation of 20~30 mg / L organic dye wastewater. Therefore, the present invention not only improves the degradation efficiency, but can also be used for the efficient degradation of high-concentration organic dye wastewater, providing an efficient treatment method for the treatment of high-concentration organic dye wastewater.

[0019] (3) The present invention provides a new idea for the friction catalytic degradation of organic dye wastewater by titanium dioxide nanopowder, and also provides a new application direction for alumina ceramic sheets. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is the XRD diagram of the titanium dioxide nanopowder used in the present invention.

[0021] Figure 2 HRTEM images of the titanium dioxide nanopowder used in the present invention, wherein (a) is a morphology image of the titanium dioxide nanopowder, and (b) is a lattice fringe image of the titanium dioxide nanopowder.

[0022] Figure 3 1 is a graph showing the change in absorbance of the methyl orange solution or the methylene blue solution over the reaction time in Examples 1 to 6 of the present invention, wherein (a), (b), (c), (d), (e), and (f) correspond to Example 1, Example 2, Example 3, Example 4, Example 5, and Example 6, respectively.

[0023] Figure 4 It is a curve showing the change of the ratio of the absorbance of the remaining methylene blue in the solution under the action of different scavengers to the absorbance of the initial methylene blue solution as a function of the reaction time in the capture experiment.

[0024] Figure 5 This is a physical electronic photograph of an alumina substrate. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The titanium dioxide nanopowder used in the present invention is purchased from Shanghai MacLean Biochemical Technology Co., Ltd. The X-ray diffraction (XRD) spectrum of the titanium dioxide nanopowder is as follows: Figure 1 Compared with the standard diffraction peaks of the XRD card library with card number PDF#21-1272, the (101), (103), (004) and (112) crystal planes almost completely coincide with the peaks at 25°, 36°, 37° and 38° on the card. The titanium dioxide nanopowder used is anatase phase and has high purity.

[0027] The titanium dioxide nanopowders were characterized by high-resolution transmission electron microscopy (HRTEM). Figure 2 As shown, Figure 2 (a) is the morphology of titanium dioxide nanopowder, which shows that the size of titanium dioxide nanopowder is highly uniform, with a particle size of 30-50 nm, complete particle crystallinity, and obvious boundaries can be observed. (b) in Figure 2 is the lattice fringe image of titanium dioxide nanopowder, where the lattice fringe of titanium dioxide can be clearly seen. The lattice spacing calculated by DM lattice calibration software is 0.316 nm, which perfectly matches the (101) crystal plane spacing of the anatase phase.

[0028] The present invention is described in detail with specific embodiments below. For the specific conditions not specified in the following embodiments, all operations shall be carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials and reagents used without indicating the manufacturer are all conventional products that can be purchased commercially. The magnetic turntable used in the following embodiments adopts the magnetic turntable disclosed with patent number 202011431424.5 or patent number 202022946950.7. The titanium substrate used is a metal sheet made of titanium, and the titanium substrate in the embodiment is purchased from Bodun Cemented Carbide Co., Ltd. The alumina substrate used is a ceramic sheet made of alumina, and the alumina substrate in the embodiment is purchased from Zhuhai Huiyou Electronics Co., Ltd. The actual electronic photograph of the alumina substrate is shown in the figure. Figure 5 As shown, Figure 5 The titanium substrate or the aluminum substrate may be pasted with commercially available 502 glue in the embodiment, but this description is not considered as a limitation of the present invention.

[0029] Example 1 30 mL of 30 mg / L methyl orange solution was added to a flat-bottomed glass beaker (the bottom of the flat-bottomed glass beaker was not attached with a titanium substrate or an alumina substrate). The flat-bottomed glass beaker was 75 mm high, had a round bottom, and had a bottom diameter of 50 mm. A magnetic turntable was then added to the flat-bottomed glass beaker, and 300 mg of titanium dioxide nanopowder was added. The flat-bottomed glass beaker was placed in a dark environment at room temperature (25°C), and the reaction was stirred at 400 rpm on a magnetic stirrer. 3 mL of the suspension was centrifuged every 30 minutes to obtain a supernatant. The absorption spectrum of the supernatant was detected using an ultraviolet-visible spectrophotometer (UV-2550; Shimadzu, Kyoto, Japan). The results are shown in FIG. Figure 3 As shown in (a).

[0030] Example 2 A circular titanium substrate is pasted on the bottom of a flat-bottomed glass beaker. The flat-bottomed glass beaker is 75 mm high, has a circular bottom, and a bottom diameter of 50 mm. The circular titanium substrate is a circular metal sheet made of titanium. The diameter of the circular titanium substrate is 40 mm and the thickness is 1 mm. After the adhesive between the titanium substrate and the bottom of the flat-bottomed glass beaker is dried and solidified, 30 mL of 30 mg / L methyl orange solution is added to the flat-bottomed glass beaker, and then a magnetic turntable is added, and 300 mg of titanium dioxide nanopowder is added. The flat-bottomed glass beaker is placed in a dark environment at room temperature (25°C), and the reaction is stirred at 400 rpm on a magnetic stirrer. 3 mL of the suspension is centrifuged every 30 min to obtain the supernatant. The absorption spectrum of the supernatant is detected using a UV-visible spectrophotometer (UV-2550; Shimadzu, Kyoto, Japan). The results are as follows: Figure 3 As shown in (b).

[0031] Example 3 A circular alumina substrate was pasted on the bottom of a flat-bottomed glass beaker. The flat-bottomed glass beaker was 75 mm high, with a circular bottom and a bottom diameter of 50 mm. The circular alumina substrate was a circular alumina ceramic sheet made of alumina. The diameter of the circular alumina substrate was 40 mm and the thickness was 1 mm. After the glue between the alumina substrate and the bottom of the flat-bottomed glass beaker was dried and solidified, 30 mL of 30 mg / L methyl orange solution was added to the flat-bottomed glass beaker, and then a magnetic turntable was added, and 300 mg of titanium dioxide nanopowder was added. The flat-bottomed glass beaker was placed in a dark environment at room temperature (25°C), and the reaction was stirred at 400 rpm on a magnetic stirrer. 3 mL of the suspension was centrifuged every 30 min to obtain the supernatant. The absorption spectrum of the supernatant was detected using an ultraviolet-visible spectrophotometer (UV-2550; Shimadzu, Kyoto, Japan). The results are as follows: Figure 3 As shown in (c).

[0032] Example 4 30 mL of 30 mg / L methyl orange solution was replaced with 30 mL of 20 mg / L methylene blue solution. The rest was the same as in Example 1. The absorption spectrum of the supernatant was measured using an ultraviolet-visible spectrophotometer (UV-2550; Shimadzu, Kyoto, Japan). The results are as follows: Figure 3 As shown in (d).

[0033] Example 5 30 mL of 30 mg / L methyl orange solution was replaced with 30 mL of 20 mg / L methylene blue solution. The rest was the same as in Example 2. The absorption spectrum of the supernatant was measured using an ultraviolet-visible spectrophotometer (UV-2550; Shimadzu, Kyoto, Japan). The results are as follows: Figure 3 As shown in (e).

[0034] Example 6 30 mL of 30 mg / L methyl orange solution was replaced with 30 mL of 20 mg / L methylene blue solution. The rest was the same as in Example 3. The absorption spectrum of the supernatant was measured using an ultraviolet-visible spectrophotometer (UV-2550; Shimadzu, Kyoto, Japan). The results are as follows: Figure 3 As shown in (f).

[0035] Depend on Figure 3 It can be seen that the friction catalytic degradation of 30 mg / L methyl orange (MO) solution using titanium dioxide nanopowder, in the friction catalytic degradation process, the bottom substrate material of the reaction container used in Example 1 is glass, and titanium dioxide nanopowder is used under the glass substrate to friction catalytically degrade 30 mL 30 mg / L methyl orange solution, and the time for methyl orange to be almost completely degraded is 420 min. For the same volume and concentration of methyl orange solution, the same amount of titanium dioxide nanopowder added, the bottom of the reaction container used in Example 2 is a titanium metal sheet as a substrate, and titanium dioxide nanopowder is used under the titanium substrate to friction catalytically degrade 30 mL 30 mg / L methyl orange solution, and the time for methyl orange to be almost completely degraded is shortened to 360 min. Under the same conditions, the bottom of the reaction container used in Example 3 is alumina ceramic sheet as a substrate, and titanium dioxide nanopowder is used under the alumina substrate to friction catalytically degrade 30 mL 30 mg / L methyl orange solution, and the time for methyl orange to be almost completely degraded is shortened to 120 min.

[0036] Similarly, for 30 mL 20 mg / L methylene blue solution, the bottom substrate material of the reaction container used in Example 1 is glass, and titanium dioxide nanopowder is used to frictionally catalyze the degradation of 30 mL 20 mg / L methylene blue solution under the glass substrate, and the time for methylene blue to be almost completely degraded is 15 h. For the same volume and concentration of methylene blue solution, the same amount of titanium dioxide nanopowder is added, and the bottom of the reaction container used in Example 2 is titanium metal sheet as a substrate, and titanium dioxide nanopowder is used to frictionally catalyze the degradation of 30 mL 20 mg / L methylene blue solution under the titanium substrate, and the time for methylene blue to be almost completely degraded is shortened to 4.5 h. Under the same conditions, the bottom of the reaction container used in Example 3 is alumina ceramic sheet as a substrate, and titanium dioxide nanopowder is used to frictionally catalyze the degradation of 30 mL 20 mg / L methylene blue solution under the alumina substrate, and the time for methylene blue to be almost completely degraded is shortened to 2.5 h.

[0037] It can be seen that in the system of friction-catalytic degradation of methyl orange or methylene blue wastewater by titanium dioxide nanopowder, using alumina ceramic sheets as substrates at the bottom of the reaction container can greatly increase the degradation rate of methyl orange or methylene blue, thereby shortening the time for complete degradation of methyl orange or methylene blue. It can be seen that alumina substrates can promote the friction-catalytic degradation process and have great application potential in organic dye wastewater treatment systems.

[0038] The present invention utilizes friction catalysis technology to degrade organic dye wastewater, utilizes titanium dioxide nanopowder as catalyst, and uses alumina ceramic sheet as substrate. During the friction catalysis process, the titanium dioxide nanopowder and the alumina substrate rub against each other, causing local charge transfer and energy change on the substrate, and stimulating the electron transition of the titanium dioxide nanopowder to generate highly active electron-hole pairs, and generate hydroxyl free radicals (·OH) and superoxide free radicals (·O2 - ) and other active substances, which can oxidize and decompose many organic pollutants, thereby achieving the degradation of organic pollutants.

[0039] In order to explore the active substances that degrade organic pollutants, the present invention also carried out a capture test, specifically: take five flat-bottomed glass beakers (the flat-bottomed glass beaker is 75 mm high, the bottom is round, and the bottom diameter is 50 mm), respectively labeled A, B, C, D, and E, and paste an alumina ceramic sheet with a diameter of 40 mm and a thickness of 1 mm on the bottom of each flat-bottomed glass beaker as a substrate, and add 30 mL of 20 mg / L methylene blue solution, a magnetic turntable and 300 mg of titanium dioxide nanopowder to each flat-bottomed glass beaker, and then add 0.03 mmol BQ (p-benzoquinone) as a free radical scavenger to the flat-bottomed glass beaker A, add 0.03 mmol EDTA-2Na (disodium ethylenediaminetetraacetic acid) as a free radical scavenger to the flat-bottomed glass beaker B, and add 0.03 mmol TBA (tert-butyl alcohol) to the flat-bottomed glass beaker C. As a free radical scavenger, 0.03mmolAgNO3 was added to a flat-bottomed glass beaker D as a free radical scavenger. Free radical scavengers BQ (p-benzoquinone), EDTA-2Na (disodium ethylenediaminetetraacetic acid), TBA (tert-butyl alcohol), and AgNO3 were used to capture superoxide radicals (·O2 - ), holes h⁺, hydroxyl radicals (·OH), e⁻ electrons. Flat-bottomed glass beakers A, B, C, D, and E were placed in a dark environment at room temperature (25°C), and stirred on a magnetic stirrer at 400 rpm for reaction. 3 mL of the suspension was centrifuged every 30 min to obtain the supernatant. The absorbance A of the supernatant was detected using an ultraviolet-visible spectrophotometer (UV-2550; Shimadzu, Kyoto, Japan). A / A0 was used as the ordinate (A0 was the initial absorbance of the 20 mg / L methylene blue solution) and the stirring time t (min) was used as the abscissa to plot the ratio of the absorbance (A) of the remaining methylene blue in the solution under the action of different free radical scavengers to the absorbance of the initial methylene blue solution (A0). The curve of the ratio A / A0 versus the stirring time t (min) was obtained, as shown in the figure. Figure 4 As shown. It can be seen that after adding 0.03mmol TBA (tert-butanol) to the flat-bottomed glass beaker C, the degradation rate of methylene blue is extremely low. After 150 minutes of degradation, the A / A0 value is still very high, indicating that the active substance produced by the friction catalytic reaction that plays a major role in the degradation of methylene blue is captured by TBA (tert-butanol), and the corresponding active substance captured by TBA (tert-butanol) is hydroxyl radical (·OH). Therefore, the active substance that plays a major role in the degradation of methylene blue is hydroxyl radical (·OH). In addition, after adding BQ (p-benzoquinone) to the flat-bottomed glass beaker A, the degradation rate of methylene blue is also reduced. The corresponding active substance captured by BQ (p-benzoquinone) is superoxide radical (·O2 - ), indicating that superoxide radicals (·O2 -) also has a certain degradation effect on methylene blue.

[0040] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. Application of alumina substrate in tribocatalytic degradation of high-concentration organic dye wastewater.

2. The use according to claim 1, characterized in that: The alumina substrate is an alumina ceramic sheet.

3. The use according to claim 2, characterized in that: The thickness of the alumina ceramic sheet is 1 mm.

4. The use according to claim 2, characterized in that: Using alumina ceramic sheets as substrates and titanium dioxide nanopowder as catalysts, friction catalysis is used to achieve the degradation of organic dye wastewater.

5. The use according to claim 1 or 2, characterized in that: The specific method includes: fixing an alumina substrate at the bottom of a flat-bottomed glass beaker, then adding organic dye wastewater, a magnetic turntable and titanium dioxide nanopowder into the flat-bottomed glass beaker, then placing the flat-bottomed glass beaker in a dark environment at room temperature, stirring the reaction on a magnetic stirrer for 90 to 150 minutes, and after the reaction is completed, the organic dye in the wastewater is completely degraded.

6. The use according to claim 5, characterized in that: The concentration of organic dyes in organic dye wastewater is 20~30mg / L.

7. The use according to claim 5, characterized in that: The organic dye in the organic dye wastewater is at least methyl orange or methylene blue.

8. The use according to claim 5, characterized in that: The speed of the magnetic stirrer was set to 400 rpm.

9. The use according to claim 5, characterized in that: The mass ratio of titanium dioxide nanopowder to the volume of organic dye wastewater is 10 mg: 1 mL.

10. The use according to claim 5, characterized in that: The particle size of titanium dioxide nanopowder is 30~50 nm.

Citation Information

Patent Citations

  • Magnetic rotating disk for tribocatalysis of semiconductor powder

    CN114602398B

  • Magnetic turntable for friction catalysis of semiconductor powder

    CN214716540U

  • Parallel-arrangement graphene ceramic high-performance friction material and low-cost preparation method

    CN108623292A

  • Pollutant treatment method based on friction catalysis of semiconductor powder

    CN109850983A

  • Preparation and application method of long-life friction-sensitive graphdiyne-based piezoelectric material

    CN111495351A

Cited By

  • Method for degrading organic pollutants in sewage through friction catalysis and application of method

    CN120364836A

  • Method for catalytic degradation of organic pollutants in wastewater by friction and application thereof

    CN120364836B

  • Device and method for synergistically degrading pollutants through friction coupling photocatalysis

    CN120423637A